Leonardville and Riley, Riley County - Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2010)
Two towns located five miles apart make for instant rivals. Located in Riley County, the towns of Leonardville and Riley competed to establish a post office and attract the attention of a railroad. Leonardville won the first battle and boomed while for several years the town of Riley struggled to survive. The town of Riley was revived when the Rock Island railroad connected Bala, Riley and Keats. From that point, the two towns competed on most everything from church building to school sports. In 1959 consolidation forced the two communities together to form one district. A new high school was built half-way between the two towns. The new district was called Riley County Schools, not Riley and not Leonardville.
Angela Schnee, “Leonardville and Riley, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/8.
Keywords: Hair Brothers; Kevin Larson; Leonardville; Little Kansas Wiggler; Riley; Riley County